NATIVE AMERICAN REPRESENTATION IN SHERMAN ALEXIE’S SHORT STORY THE TRIAL OF THOMAS BUILDS-THE-FIRE - Mike Wijaya Saragih (Prodi Sastra Inggris UKI, 2021)
Abstract This paper aims to show the representation of Native Americans in Sherman Alexie's short story The Trial of Thomas-Builds-the-Fire, which is part of his story collections The Lone Ranger and Tonto Fistfight in Heaven (1993). The main character, Thomas-Builds-the-Fire, represents native Americans. This paper will analyze Thomas as a subaltern who was oppressed by white hegemony. The presence of fairy tales as media voicing out Thomas' thoughts and feeling as the subaltern interprets something deeper. The present writer will use Gayatri C. Spivak's theories which are subaltern and representation, to analyze the forms of Native American representation. The result shows there are two forms of representation used in the story. They are